POLA DAN PERILAKU KONSUMSI RUMAH TANGGA DALAM PERSPEKTIF EKONOMI ISLAM DI KOTA MAKASSAR - Supatminingsih, Tuti (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2018)
This study discusses the pattern and behavior of household consumption in Islamic economic perspective in Makassar city. The results showed that the type of household consumption in Makassar City, dominated by expenditure for nonfood. Income, education, number of family members, number of family members, saving, credit, employment status of head of household simultaneously have a significant influence on household consumption expenditure in Makassar City. Household income, number of working family members, saving, and credit, partially have a significant effect on household consumption expenditure in Makassar City, whereas the education of head of household, the number of family member, occupation of head of household have influence which is insignificant to household consumption expenditure in Makassar City. The behavior of the family household consumption in Makassar City based on the perspective of Islamic economics, firstly, the purchase of food and non-food goods in line with the concept of needs, which is the need for more priority and has paid attention to the religious teachings of Islam; secondly, the mashlahah that is achieved with the fulfillment of food and non food needs is the acquisition of utility and blessing in consuming food and non food, thirdly, the benefits gained not only in the world but in the hereafter also, because in consumption expenditure there are still social aspects, such as zakat, infaqandsedakah, so that consumption activities that carried were based on religious values.